2014
DOI: 10.1097/ta.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and platelet contributions to clot formation

Abstract: BACKGROUND Thromboelastography (TEG) is used to diagnose perturbations in clot formation and lysis that are characteristic of acute traumatic coagulopathy (ATC). With novel functional fibrinogen (FF) TEG, fibrin- and platelet-based contributions to clot formation can be elucidated to tailor resuscitation and thromboprophylaxis. We sought to describe the longitudinal contributions of fibrinogen and platelets to clot strength after injury, hypothesizing that low levels of functional fibrinogen and a low contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 28 publications
4
63
0
Order By: Relevance
“…Using this technology, human studies have shown that these tests are able to detect hypercoagulable states missed by common coagulation parameters such as plasma prothrombin time or activated partial thromboplastin time [34], and furthermore, that increased clot firmness on admission thromboelastography predicts increased rates of pulmonary embolism [35], highlighting the clinical importance of these tests. In addition, similar to our murine study, other human studies have shown that platelet contribution to clot strength steadily decreases over the 72 h after trauma, with a resulting increase in fibrinogen contribution [31]. Animal models have investigated altered platelet function after head injury [36]; however, our study is the first to demonstrate similar temporal changes in coagulation, specifically the platelet contribution to clot strength, after TBI using thromboelastometry in a murine model.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Using this technology, human studies have shown that these tests are able to detect hypercoagulable states missed by common coagulation parameters such as plasma prothrombin time or activated partial thromboplastin time [34], and furthermore, that increased clot firmness on admission thromboelastography predicts increased rates of pulmonary embolism [35], highlighting the clinical importance of these tests. In addition, similar to our murine study, other human studies have shown that platelet contribution to clot strength steadily decreases over the 72 h after trauma, with a resulting increase in fibrinogen contribution [31]. Animal models have investigated altered platelet function after head injury [36]; however, our study is the first to demonstrate similar temporal changes in coagulation, specifically the platelet contribution to clot strength, after TBI using thromboelastometry in a murine model.…”
Section: Discussionsupporting
confidence: 83%
“…MPs were isolated as described in section 2.5. Percent of platelet contribution (%MCF-Platelet) was calculated by the equation: (EXTEM MCF – FIBTEM MCF )/EXTEM MCF , similar to the methods used by Kornblith et al [31]. For NATEM analysis, sham mice ( n = 9) and TBI mice at 10 min ( n = 7), 24 h ( n = 10), and 72 h ( n = 11) were used.…”
Section: Methodsmentioning
confidence: 99%
“…In trauma, patients with lower functional fibrinogen had greater had greater transfusion requirements and higher mortality. [25] Rourke demonstrated that fibrinogen is rapidly depleted after trauma and that low fibrinogen levels predicted increased mortality at 24 hours. [26] Table 4 lists studies of fibrinogen depletion in trauma.…”
Section: Coagulopathy In Traumamentioning
confidence: 99%
“…Finally, in the propagation phase, the platelet now adhered to the damaged endovasculature, acts as a foundation for thrombin conversion of fibrinogen and eventual strengthening of the hemostatic clot. Kornblith et al [32] used viscoelastic testing to determine contributions of fibrinogen and platelets to maximum clot firmness in 251 trauma patients (median ISS 9, BD −3.1, INR 1.1). In this cohort, platelets contributed 69.5 % and fibrinogen 30.5 % to clot strength.…”
Section: Mechanism Of Early Ticmentioning
confidence: 99%
“…Though viscoelastic testing is “poised to replace traditional plasma-based tests in the diagnosis of perturbations in clot formation and lysis characteristic of ATC” [32], it still has many limitations. Traditional TEG as an indicator of whole blood coagulation can be improved upon by modifications that result in faster turnaround times and more specific information as to which component of coagulation is dysfunctional or deficient.…”
Section: Limitationsmentioning
confidence: 99%